Improving Attributes of Teacher Education: An Analysis - Amandeep, Dr. (SMART MOVES JOURNAL IJELLH, 2020)
Teacher education has been a cause of serious concern. Despite several commission and committees the state of affairs in these schools and colleges of education remains pretty much the same as it used to be three or even four decades ago. The paper analyses the new practices, policies and procedures in the area of teacher education that affect the quality of teacher education and accordingly the education and the nation. The attempt here is to describe several innovations that have been introduced in this field for instance NCTE, continuing Education and its centres, correspondence Education, experiments, Technology, Microteaching, UGC Panel on Teacher Education and population Education etc. These methods are indicative that the role and responsibility of the teacher is vital for the individual personality and socio-scientific as well as socio-cultural progress of society and humanity.